Bilateral detachment of the neurosensory retina in an apparently asymptomatic woman. Issue 7 (July 2021) - Brambati, Maria; Borrelli, Enrico; Trevisani, Francesco; Bruschi, Elena; Bandello, Francesco; Querques, Giuseppe
Abstract : N/A: Systemic hypertension is related to a variety of retinal manifestations. Reported herein is a case of malignant hypertension associated with bilateral foveal neurosensory detachment in a middle age woman with stenosis of the left renal artery. The present case outlines the importance of recognizing ocular manifestations as a possible consequence of life-threatening systemic disease.